2008
DOI: 10.1016/j.fishres.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

A model of meta-population dynamics for North Sea and West of Scotland cod—The dynamic consequences of natal fidelity

Abstract: It is clear from a variety of data that cod (Gadus morhua) in the North Sea do not constitute a homogeneous population that will rapidly redistribute in response to local variability in exploitation. Hence, local exploitation has the potential to deplete local populations, perhaps to the extent that depensation occurs and recovery is impossible without recolonisation from other areas, with consequent loss of genetic diversity. The oceanographic, biological and behavioural processes which maintain the spatial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 60 publications
(69 reference statements)
2
57
1
Order By: Relevance
“…Schindler et al 2010). Under conditions of locally adapted populations, abundance recovery after a local extinction may take a long time and probably a lot longer than the time estimated by models that do not take into account the spatial and genetic structure of the populations (Hutchings 2000, Heath et al 2008, Murawski 2010. These consequences highlight the relevance of maintaining the 'biocomplexity' of exploited populations.…”
Section: Consequencesmentioning
confidence: 99%
“…Schindler et al 2010). Under conditions of locally adapted populations, abundance recovery after a local extinction may take a long time and probably a lot longer than the time estimated by models that do not take into account the spatial and genetic structure of the populations (Hutchings 2000, Heath et al 2008, Murawski 2010. These consequences highlight the relevance of maintaining the 'biocomplexity' of exploited populations.…”
Section: Consequencesmentioning
confidence: 99%
“…However, the young are not spread by random all over the NS (e.g. Heath et al 2008, Gröger et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Based on microsatellite DNA markers, Hutchinson et al (2001) found 4 genetically distinct groups. Advection patterns indicate that cod in the southern NS (the German Bight, the Dogger Bank and the Southern Bight) are quite isolated from cod in the remaining NS (Heath et al 2008). Also, the elemental signature of the otoliths indicates that most adults originate from local nursery areas, and that there does not appear to be detectable exchange between spawning areas > 200 km apart (Wright et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations